The genus Ugandatrichia Mosely (Trichoptera, Hydroptilidae) in Japan - Ito, Tomiko; Ohkawa, Ayuko (Zootaxa, 2012)
The tropical-subtropical caddisfly genus Ugandatrichia Mosely (Hydroptilidae) is recorded from Japan for the first time,with 2 species. Ugandatrichia nakijinensis Ito sp. nov. is described from Okinawa-jima and Amami-oshima, in the southof Japan, based on adults and immature stages. Ugandatrichia taiwanensis Hsu and Chen, originally described fromTaiwan, is recorded and redescribed based on material from Iriomote-jima and Ishigaki-jima, in the southernmost part of Japan. Larvae of both live on smooth rock surfaces in very fast flowing waters.